2018
DOI: 10.1590/0103-1104201811610
|View full text |Cite
|
Sign up to set email alerts
|

As influências da raça/cor nos desfechos obstétricos e neonatais desfavoráveis

Abstract: This is a cross-sectional study, which evaluated race/color influences on unfavorable obstetric and neonatal outcomes. Logistic regression models were constructed to calculate the odds ratio and to examine maternal and neonatal risk. Black pregnant women prevailed with statistical significance among those with low schooling, previous hypertension, three or more living children and with occupation. Black pregnant women presented no greater risk in unfavorable outcomes. Race/color does not behave as a genetic or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1
22

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 21 publications
2
8
1
22
Order By: Relevance
“…Researchers from the compiled literature found that there is an important association of children with low birth weight for deformations, certainly the incidence will be higher in the number of cases when compared to microsomal newborns. 14,1 Regarding gender, it was observed in a study conducted in a maternity hospital in Recife (PE), that of the 113 children with congenital malformation, 46.9% were male and 53.1 female, 15 information not similar to this study according to Table 02. Studies pertinent to this theme showed no statistical relationship between malformations and gender of the child.…”
Section: Resuméncontrasting
confidence: 52%
“…Researchers from the compiled literature found that there is an important association of children with low birth weight for deformations, certainly the incidence will be higher in the number of cases when compared to microsomal newborns. 14,1 Regarding gender, it was observed in a study conducted in a maternity hospital in Recife (PE), that of the 113 children with congenital malformation, 46.9% were male and 53.1 female, 15 information not similar to this study according to Table 02. Studies pertinent to this theme showed no statistical relationship between malformations and gender of the child.…”
Section: Resuméncontrasting
confidence: 52%
“…Fortaleza (CE), Brasil. 5 https://orcid.org/0000-0002-3030-2216 7 Grupo de Pesquisa Saúde da Mulher e Enfermagem/GRUPESME. Fortaleza (CE), Brasil.…”
Section: Introductionunclassified
“…Fortaleza (CE), Brasil. 7 https://orcid.org/0000-0002-5743-1819 *Artigo extraído do trabalho de conclusão de curso << Conhecimento de puérperas sobre boas práticas oferecidas em centro de parto normalTítulo >>. Faculdade Terra Nordeste/FATENE, 2018.…”
Section: Introductionunclassified
“…Alguns estudos têm utilizado raça/cor para avaliar as iniquidades em saúde e também para identificar diferenças na idade gestacional e prematuridade entre as raças e os grupos étnicos (SØRBYE et al, 2016;PACHECO et al, 2018). Brasil, a cesariana tem sido utilizada de maneira rotineira, muitas vezes realizada de forma eletiva com horários e dias agendados, de forma mais conveniente para médicos e mães (OLIVEIRA et al, 2016).…”
Section: Discussionunclassified